1987
DOI: 10.1016/0014-5793(87)80113-8
|View full text |Cite
|
Sign up to set email alerts
|

Is phylloquinone an obligate electron carrier in photosystem I?

Abstract: Comparative quantitative analysis of phylloquinone content and photochemically competent P-700 has been performed on photosystem I particles subjected to photolysis with ultraviolet irradiation. Nonirradiated control particles exhibit a phylloquinone/P-700 stoichiometry of 1.9 + 0.2. Photolysis of the photosystem I particles induces a progressive depletion of phylloquinone, however, photochemistry as assayed at room temperature by the photooxidation of P-700 is unaffected. These data are not consistent with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
2

Year Published

1988
1988
1993
1993

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 20 publications
(24 reference statements)
4
16
2
Order By: Relevance
“…The light source, Blak Ray model B 100A (Ultraviolet Products, San Gabriel, CA) provided wavelengths of 300-400 nm at an intensity of 50 W. m -2. These conditions were similar to those used by Palace et al [9].…”
Section: Uv Irradiationmentioning
confidence: 70%
See 2 more Smart Citations
“…The light source, Blak Ray model B 100A (Ultraviolet Products, San Gabriel, CA) provided wavelengths of 300-400 nm at an intensity of 50 W. m -2. These conditions were similar to those used by Palace et al [9].…”
Section: Uv Irradiationmentioning
confidence: 70%
“…The decay halftime for the optical transient in the control preparation was -30 ms and can be assumed to be due to the recombination between P700 + and the reduced terminal acceptors FA/FB [1]. After vitamin K1 depletion (lower trace), the optical transient still showed a slow recombination in confirmation of [9] but the decay halftime was longer. Fig.2 (upper panel) shows that, during the irradiation treatment, the decay halftime of the transient increased to -60 ms, and upon more detailed analysis, we found that this was due to the introduction of a slower decay component with a halftime of approx.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have shown [7] the extraction of VK~ did not totally stop the light-induced reduction of FeS centers at 10 K. The flash yield of FeS reduction was found to suppress only 50°7o by the extraction of VK~ at 15 K [171. Another argument comes from the fact that the attempted destruction of VK~ by UV light did not inhibit PSI photochemistry [18,19].…”
Section: P700 ÷ Aoaifxfbf~mentioning
confidence: 99%
“…Some arguments against the function of phylloquinone, however, still remain ~ [16,17] and its binding site has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%